Coloring the universe : an insider's look at making spectacular images of space - Rector, Travis A. (Travis Arthur); Arcand, Kimberly, 1975-; Watzke, Megan K. (University of Alaska Press, 2015)
With a fleet of telescopes in space and giant observatories on the ground, professional astronomers produce hundreds of spectacular images of space every year. These colorful pictures have become infused into popular culture and can found everywhere, from advertising to television shows to memes. But they also invite questions: Is this what outer space really looks like? Are the colors real? And how do these images get from the stars to our screens? Coloring the Universe uses accessible language to describe how these giant telescopes work, what scientists learn with them, and how they are used to make color images. It talks about how otherwise un-seeable rays, such as radio waves, infrared light, X-rays, and gamma rays, are turned into recognizable colors. And it is filled with fantastic images taken in far-away pockets of the universe. Informative and beautiful, Coloring the Universe will give space fans of all levels an insider's look at how scientists bring deep space into brilliant focus.